Development and Innovation of Exterior Shading Devices for Climate Responsive Architecture - Phattanawasin, Srisak; Lopkerd, Prittiporn (Journal of Architectural/Planning Research and Studies (JARS), 2015)
The current energy crisis and global warming drive many issues of architectural practice and research fields including sustainable architecture and design guidelines for environmentally friendly. The effective strategy of reducing the solar radiation passing into the building, is to design building skins responsive to the climate and radiation from the sun. However, today few of intelligent systems imparted to the responsive building skins, have been already invented and selling, unfortunately, these equipments cannot be offered to all consumers, but only for the high-end projects due to their high technology process and expensive cost as mostly the same as other eco-friendly products in the market, especially in Thailand. The question arises as to whether it is possible to develop the climate responsive building skins by low-cost technology. This article aims to review the developments of climate responsive building skins in term of solar shading device, and to propose the innovation of automatically adjustable sun louvers with real-time solar tracking systems. Enhancing the efficiency of solar radiation protection into the building, the operable sun louvers can be gained the indirect natural daylight in the same time. With emphasis in the low-cost technology, this product is composed of light weight steel blades installed with inexpensive adjustable prefab hinges, solar tracker system with sensor of LDR (Light Dependent Resistors), and local microcontroller board. This climate responsive sun louvers with simple, uncomplicated, and economical systems can be integrated into both existing buildings and new design buildings, and be an ideal part of the “green” architectural solution affordable for every single households.